2023
DOI: 10.1128/spectrum.04740-22
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of Invasive Cutibacterium acnes Isolates from Deep-Seated Infections

Abstract: Opportunistic infections emerging from human skin microbiota are of ever-increasing importance. Cutibacterium acnes , being abundant on the human skin, may cause deep-seated infections (e.g., device-associated infections). Differentiation between invasive (i.e., clinically significant) C. acnes isolates and sole contaminants is often difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…All six pathogen helper C. acnes strains did not show any skin symptoms when intradermally infected alone. The lack of pathogenesis in pathogen helper C. acnes was also supported by MLST analysis, demonstrating that among the six C. acnes strains, five consisted of the IB type, which has been previously reported as the predominant commensal phylogroup 50 52 . Our data additionally revealed that C. acnes can not only promote S. aureus growth but also worsen symptoms of skin infection.…”
Section: Discussionsupporting
confidence: 66%
“…All six pathogen helper C. acnes strains did not show any skin symptoms when intradermally infected alone. The lack of pathogenesis in pathogen helper C. acnes was also supported by MLST analysis, demonstrating that among the six C. acnes strains, five consisted of the IB type, which has been previously reported as the predominant commensal phylogroup 50 52 . Our data additionally revealed that C. acnes can not only promote S. aureus growth but also worsen symptoms of skin infection.…”
Section: Discussionsupporting
confidence: 66%
“…C. acnes is generally composed of several phylogenetic subtypes, commonly referred to as IA 1 , IA 2 , IB, IC, II, III 17 . At the genome level, even finer classifications are possible 17,39 . In this study, a genetic analysis was conducted to determine the phylotype ratio of C. acnes in all subjects.…”
Section: Discussionmentioning
confidence: 99%